1999
DOI: 10.1161/01.cir.100.23.2332
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Continuous Positive Airway Pressure Decreases Daytime Sympathetic Traffic in Obstructive Sleep Apnea

Abstract: Background-Patients with obstructive sleep apnea (OSA) have high levels of muscle sympathetic nerve activity (MSNA).We tested the hypothesis that long-term continuous positive airway pressure (CPAP) treatment will decrease MSNA in OSA patients. Methods and Results-We measured blood pressure, heart rate, and MSNA in 11 normotensive, otherwise healthy patients with OSA who were treated with CPAP. The measurements were obtained at baseline and after 1 month, 6 months, and 1 year of CPAP treatment. These measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
218
0
22

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(263 citation statements)
references
References 40 publications
18
218
0
22
Order By: Relevance
“…The mechanism for improved LVEF with chronic CPAP therapy in patients with CHF and OSA likely relates to improved systolic function due to a favourable modification of the pathophysiology of left ventricular dysfunction. Previous investigators have documented excessive sympathetic nervous system activity in patients with OSA and CHF that can be attenuated by CPAP therapy (11,12,14,15,24,54,55). In this regard, we observed a relationship between baseline SVRI and the recovery of systolic function.…”
Section: Velocity (E) To Ea Ratio (Bottom) Ns Nonsignificantsupporting
confidence: 69%
See 1 more Smart Citation
“…The mechanism for improved LVEF with chronic CPAP therapy in patients with CHF and OSA likely relates to improved systolic function due to a favourable modification of the pathophysiology of left ventricular dysfunction. Previous investigators have documented excessive sympathetic nervous system activity in patients with OSA and CHF that can be attenuated by CPAP therapy (11,12,14,15,24,54,55). In this regard, we observed a relationship between baseline SVRI and the recovery of systolic function.…”
Section: Velocity (E) To Ea Ratio (Bottom) Ns Nonsignificantsupporting
confidence: 69%
“…In addition to restoring normal sleep architecture, CPAP therapy prevents the extremes of negative intrathoracic pressure and, thus, reduces left ventricular transmural pressure, prevents recurrent hypoxia, reduces sympathetic nervous system activity, decreases blood pressure and heart rate, and increases arterial baroreceptor sensitivity and daytime heart rate variability (1,7,(10)(11)(12)(13)(14)(15)(16). In the normal heart, initiation of CPAP therapy acutely increases intrathoracic pressure, decreases venous return and left ventricular filling, and results in decreased cardiac output (17)(18)(19).…”
mentioning
confidence: 99%
“…These cycles may occur hundreds of times a night in a patient with moderate-to-severe OSAS (13,14). Hence, both ventricles are exposed to hemodynamic stress.…”
Section: Cpap Treatment and Ecg Findings In Osasmentioning
confidence: 99%
“…8 Most changes might go back to normality once obstructive sleep apnea is treated and improved. 9,10 Sympathetic stimulation because of sustained hypoxemia is particularly insidious, 11 and although not directly measured, it is likely present also in the population sample of Avelar et al 4 as is suggested by the higher heart rate. Sympathetic hypertone can worsen insulin resistance and can modulate leptin expression in a way that facilitates the development of a vicious cycle, worsens obesity, and promotes the related comorbidities.…”
mentioning
confidence: 99%